2016
DOI: 10.1097/mcg.0000000000000686
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Effectiveness of Lactobacillus fermentum Against Different Candida Species Compared With Broadly Used Azoles

Abstract: The use of beneficial bacteria, especially lactobacilli, could be regarded as a good alternative for the prevention and treatment of Candida infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This probiotic formulation is ad hoc designed, patented, and produced by Probiotical SPA-Novara, Italy. The choice of the strains was done considering the results of previous studies that showed their capabilities to counteract gut pathogens, such as some Candida strains [15], Enterobacteria [16,17], their anti-inflammatory properties and Fig. 1 Study flowchart for baseline analysis and phase 1 trial.…”
Section: Probiotic Supplementmentioning
confidence: 99%
See 1 more Smart Citation
“…This probiotic formulation is ad hoc designed, patented, and produced by Probiotical SPA-Novara, Italy. The choice of the strains was done considering the results of previous studies that showed their capabilities to counteract gut pathogens, such as some Candida strains [15], Enterobacteria [16,17], their anti-inflammatory properties and Fig. 1 Study flowchart for baseline analysis and phase 1 trial.…”
Section: Probiotic Supplementmentioning
confidence: 99%
“…1 Study flowchart for baseline analysis and phase 1 trial. ALS, amyotrophic lateral sclerosis; T0, baseline; T1, 3 months from baseline; T2, 6 months from baseline; ALSFRS-R, ALS Functional Rating Scale-Revised; BMI, body mass index; FVC%, force vital capacity %; DGGE, denaturing gradient gel electrophoresis; qPCR, quantitative polymerase chain reaction; NGS, next-generation sequencing positive influence in restoring the gut physiological barrier [15,18].…”
Section: Probiotic Supplementmentioning
confidence: 99%
“…In the female genital tract, a healthy vaginal status is commonly associated with low microbial diversity and prevalence of Lactobacillus. Commensal vaginal Lactobacillus species are thought to defend against many pathogens, such as Candida infection [7,8], sexually transmitted diseases [9], urinary tract infections [10,11] and human immunode ciency virus (HIV) infection [12]. Bacterial vaginosis (BV) is associated with a higher risk of miscarriage, preterm premature rupture of membranes, HPV infection and sexually transmitted infections [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of microorganisms inhabit the female genital tract, and hundreds of studies have revealed that a dominance of Lactobacillus lowers bacterial richness and diversity, indicating a healthy vaginal status. A healthy microbial biofilm may prevent or hinder many urogenital diseases, such as Candida infection [5,6], sexually transmitted diseases [7], urinary tract infections [8,9] and human immunodeficiency virus (HIV) infection [10]. Some studies to date have also reported that changes in the vaginal microbial structure have a close connection with HPV infection [11][12][13][14] and CIN progression [15][16][17].…”
Section: Introductionmentioning
confidence: 99%